Мухитдинов Н., Аметов А., Альмерекова Ш., Абидкулова К. Сирек және эндем oxytropis аlmaatensis bajt. Өсімдігі ценопопуляцияларының эколого-биологиялық ерекшеліктері: д.б.н., профессор кафедры биоразнообразия и биоресурсов, e-mail: Nashtay.Muhitdinov@kaznu.kz 2к.б.н., профессор кафедры биоразнообразия и биоресурсов, e-mail: Abibulla.Ametov@kaznu.kz 3PhD-докторант кафедры биоразнообразия и биоресурсов, e-mail: almerekovakz@gmail.com 4ведущий специалист кафедры биоразнообразия и биоресурсов, e-mail: Karime.Abidkulova@kaznu.kz Казахский национальный университет имени аль-Фараби, Казахстан, г. Алматы (Eurasian Journal of Ecology, 2017)
The article is devoted to the complex study of the cenopopulations of the rare endemic speciesOxytropis almaatensis and to the cenopopulations assessment. As a result of the conducted studies, thefeatures of the ecological-cenotic confinement of the cenopopulations O.almaatensis were revealed. Allthree populations of the studied species are located on the axes of the northern macroslope of the TransIli Alatau mountains and on stony-gravel deposits along rivers occupying by small areas ranging from 1200 to 2400 m2. Studying the number, density and age spectrum, determining the general, reproductive power of the cenopopulations showed that most of them have an exceptionally high coefficient, onlythe populations of 5-6 have a bimodal spectrum with the maximum imposed vegetative and generativeindividuals. The highest density of Oxytropis almaatensis species was noted in the cenpopulation №6 –13.5±3.1 pcs./m2, the smallest in the coenopopulation №4 – 6,3±0,5 pcs./m2.As a result of the study Oxytropis almaatensis cenopopulations was revealed that they are locatedwithin their optimum, there is no special threat of extinction for this species. However, due to the factthat Oxytropis almaatensis is a narrowly endemic species with a limited range, we recommend thefollowing activities: 1) Ile-Alatau National Natural Park should keep control and constantly conductmonitoring work for all three populations of Oxytropis almaatensis in Trans-Ili Alatau mountains; 2) TheInstitute of Botany and Phytointroduction should be introduced into its collections Oxytropis almaatensis species as a narrow endemic, rare species with a limited range.Key words: Population, cenopopulation, plant communities, plant life forms, ecological types